2022
DOI: 10.3389/fimmu.2022.860689
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Test for Measuring Complement Attack on Endothelial Cells: From Research to Bedside

Abstract: As part of the innate immune system, the complement system plays a key role in defense against pathogens and in host cell homeostasis. This enzymatic cascade is rapidly triggered in the presence of activating surfaces. Physiologically, it is tightly regulated on host cells to avoid uncontrolled activation and self-damage. In cases of abnormal complement dysregulation/overactivation, the endothelium is one of the primary targets. Complement has gained momentum as a research interest in the last decade because i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Detection of the C3 activation fragments in ex vivo models of complement activation and in tissues is important for clinical practice and for understanding disease pathogenesis. Analysis of C3 activation fragments and C5b‐9 on cultured endothelial cells incubated with serum from aHUS patients closely resembles the pathophysiological context of this disease 114 . It has shown elevated deposits from the sera of patients or model conditions of aHUS, malignant hypertension, elevated liver enzymes, low platelet syndrome (HELLP syndrome), sickle cell disease, preeclampsia, lupus nephritis, etc.…”
Section: Regulation Of C3 Activationmentioning
confidence: 89%
See 1 more Smart Citation
“…Detection of the C3 activation fragments in ex vivo models of complement activation and in tissues is important for clinical practice and for understanding disease pathogenesis. Analysis of C3 activation fragments and C5b‐9 on cultured endothelial cells incubated with serum from aHUS patients closely resembles the pathophysiological context of this disease 114 . It has shown elevated deposits from the sera of patients or model conditions of aHUS, malignant hypertension, elevated liver enzymes, low platelet syndrome (HELLP syndrome), sickle cell disease, preeclampsia, lupus nephritis, etc.…”
Section: Regulation Of C3 Activationmentioning
confidence: 89%
“…Analysis of C3 activation fragments and C5b‐9 on cultured endothelial cells incubated with serum from aHUS patients closely resembles the pathophysiological context of this disease. 114 It has shown elevated deposits from the sera of patients or model conditions of aHUS, malignant hypertension, elevated liver enzymes, low platelet syndrome (HELLP syndrome), sickle cell disease, preeclampsia, lupus nephritis, etc 109 , 115 , 116 , 117 , 118 In one case, it was used to adjust the therapeutic regimen with a complement‐blocking drug, as the test showed increased deposition of C5b‐9 before the relapse of the disease, encouraging further studies. 119 To make specific diagnoses, tissue staining for C3 activation fragments is critical in clinical practice, especially on kidney biopsies.…”
Section: Regulation Of C3 Activationmentioning
confidence: 99%
“…Expression of terminal complement activation, C5b-9, in the bloodstream has not been validated as a reliable biomarker of aHUS activity [31] or relapse in patients with anti-FH antibodies [20]. However, Song et al [32] showed that C5b-9 levels increased during the acute phase and decreased during remission in a cohort of 33 positive for anti-FH patients. Determination of C5b-9 in two of our patients currently monitored to prevent possible relapse showed distinct C5b-9 expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Two principal techniques for in vitro diagnosis have been proposed, including the modified Ham assay (mHam) 9,10 and HMEC-1 staining for C5b-9 [11][12][13][14] , but neither is widely adopted. Both assays rely upon testing patient serum for abnormal cell-deposited complement activity.…”
Section: Introductionmentioning
confidence: 99%